Design of a Robotic Humanoid for Surveillance Application - David Odu Agbo; Jonathan A. Enokela; Goshwe Y. Nentawe (Future Science, 2021)
The evolution of robotics and their control systems have made the placement of arms, their motion, grasping of objects, as well as exploring their immediate environments a very important area of research. The electronic design and implementation of the humanoid which involves the keypad and graphical user interface (GUI) to track the movement of the humanoid robot as well as control the humanoid robot in performing the tasks of avoidance of obstacles and picking of objects is achieved. The system is made of two units: the remote controller unit and the humanoid control unit. The remote controller unit is of two types namely; the keypad and the GUI. The keypad uses the buttons to control or direct the humanoid while the GUI does the control using PC. The GUI has the additional function of viewing the picture taken by the humanoid, if the arrangement of an obstacle is not included among the sixteen obstacle avoidance algorithms considered. The humanoid control unit makes the humanoid walk and avoid obstacles autonomously. The simulation of robotic humanoid and hardware results also show that the hardware implementation can be embedded into the humanoid frame for surveillance applications